Triple super phosphate as a source of phosphorus in the diet of growing bull - Akter, A; Khandaker, ZH (Bangladesh Journal of Animal Science, 2012)
The study was conducted to investigate the use of Triple Super Phosphate (TSP) as a source of phosphorus in growing cattle. Twelve indigenous growing bull (initial live weight of 150 ± 10 kg) were assigned to four dietary treatments, viz. basal diet (T0) containing 0.14% P and basal diet was supplemented with TSP to provide P levels of 0.24 (T1), 0.35 (T2) and 0.45% (T3) respectively. All diets were formulated to be iso-nitrogenous and iso-energetic. Significant (P<0.05) differences in dry matter intake (DMI) were observed among the dietary treatments. The DMI (g/d) of animals fed diet having 0.35% P was higher than the diet containing 0.14, 0.24 and 0.45% P. The apparent digestibility of DM and OM were significantly (P<0.01) affected but CP and EE were not significantly (P>0.05) affected by the supplementation of P from TSP. The digestibility of CF and NFE was significantly (P<0.01) higher for diets T2 (0.35% P) compared to diet containing 0.14, 0.24 and 0.45% P. Apparent absorption of P was significantly (P<0.05) higher in animals fed on diet containing 0.14% phosphorous (T0) than diets with 0.35 and 0.45% phosphorus and true absorption (g/100g) of P was significantly (P<0.01) higher in the animals fed on diets T0 (0.14% P) than those fed on other diets (T1, T2 and T3. Phosphorus balance was significantly (P<0.01) higher for diets T1 (4.37 g/d), T2 (5.75 g/d) and T3 (7.09 g/d) compared to diet T0 (2.87 g/d) and highest value was observed on diet T3. There was no significant (P>0.05) difference among the mean values for live weight gain and the highest daily live weight gain was observed for diet T2 (69.44g) compared to the other diets T0, T1 and T3). The average serum P concentration of animals fed on diets T1, T2 and T3 was significantly higher (P<0.01) than that of animal fed on diet T0. The results suggested that supplementation of TSP as a source of phosphorus increased total DMI, digestibility of CF, NFE, P retention, P content of blood serum and live weight gain of growing calves. Therefore, supplementation of 0.21% P from TSP may be used in growing cattle ration. Key words: Phosphorus; Triple super phosphate; Growing bull DOI: http://dx.doi.org/10.3329/bjas.v39i1-2.9681 Bang. J. Anim. Sci. 2010, 39(1&2): 89-96